Dermatitis bullosa como efecto secundario a pembrolizumab - Alícia da Silva Oliveira; Emílio Macias Bravo (Sociedade Galega de Medicina Interna, 2022)
Adverse immunotherapy reactions are common and can affect virtually any organ system, with dermatological reactions, being some of the most commonly encountered. Bullous dermatitis can occur with anti-programmed cell death-1 treatment, although it is not amongst the common skin effects, it is a clinical entity that needs an accurate clinician judgement. The ideal approach is treatment discontinuation and the use of corticosteroids, with the possibility of immunotherapy reintroduction after condition resolution. We present images of a bullous dermatitis as an adverse reaction to pembrolizumab in a 48 year old patient with a diagnose of a stage IV melanoma, that presented a full recovery and continued to show a complete response to therapy, as observed using PET-CT.